2011
DOI: 10.1007/s00535-010-0368-4
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the fecal microbiota profiles between ulcerative colitis and Crohn’s disease using terminal restriction fragment length polymorphism analysis

Abstract: The fecal microbial communities of IBD patients were different from those of healthy individuals. The gut microbiota of patients with inactive UC tended to be closer to that of healthy individuals, suggesting different roles for the fecal microbiota in the pathophysiology of UC and CD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

22
130
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 194 publications
(158 citation statements)
references
References 47 publications
22
130
0
1
Order By: Relevance
“…This was further confirmed by the restoration in the population of some butyrate producers with simultaneous increase in the level of SCFA in remission samples. The results of this study supported similar observations made in earlier studies [70,85]. Therefore, alterations in the population of microbiota with respect to disease type and severity as described here may play a role as biomarkers that may help to predict disease predisposition, activity, severity, and responsiveness to therapy.…”
Section: Gut Flora and Inflammatory Bowel Diseasesupporting
confidence: 91%
See 1 more Smart Citation
“…This was further confirmed by the restoration in the population of some butyrate producers with simultaneous increase in the level of SCFA in remission samples. The results of this study supported similar observations made in earlier studies [70,85]. Therefore, alterations in the population of microbiota with respect to disease type and severity as described here may play a role as biomarkers that may help to predict disease predisposition, activity, severity, and responsiveness to therapy.…”
Section: Gut Flora and Inflammatory Bowel Diseasesupporting
confidence: 91%
“…These levels of Lactobacilli significantly reverted back to normal during remission, close to controls. Similar results have also been reported in other studies [69][70][71]. This was further supported by an increase in fecal lactate level (as measured by gas chromatography) in severe UC patients as compared to controls.…”
Section: Gut Flora and Inflammatory Bowel Diseasesupporting
confidence: 91%
“…Restricted bacterial diversity and underrepresentation of anti-inflammatory microorganisms, such as Clostridium cluster XIVa and Akkermansia muciniphila, represent typical dysbiotic features in IBD (1)(2)(3)(4). Since the intestinal microbial community performs a wide range of bile acid modifications, including deconjugation, dehydroxylation, oxidation, and epimerization (5), shifts in the composition of the gut microbiota are associated with perturbations of the fecal bile acid profile (6,7).…”
mentioning
confidence: 99%
“…Intestinal microbiota confer important functions to the host including mucosal barrier, metabolic and immune regulatory functions (151). Evidence from recent molecular studies revealed differences in the intestinal microbiome between healthy individuals and IBD patients with a reduction of beneficial and an increase of potentially dangerous bacteria (152). Current therapy for treating IBD includes the administration of aminosalicylate, steroids, immunosuppressive agents and antibiotics; although it is not curative and has several side effects (153).…”
Section: Inflammatory Bowel Disease (Ibd)mentioning
confidence: 99%